Towards a hierarchical framework for predicting the best answer in a question answering system - Chua, Alton Yeow Kuan (2009)
This research aims to develop a model for identifying predictive variables for the selection of the best quality answer in a question-answering (QA) system. It was found that accuracy, completeness and relevance are strong predictors of the quality of the answer.